Hubungan Kepatuhan Oral Hygiene dengan Keparahan Mukositis Oral pada Pasien Kemoterapi - Dwinda Yuliana Putri; Miftafu Darussalam (Jurnal Indonesia Sehat, 2026)
Background: The World Health Organization estimates that the global burden of cancer continues to increase. Chemotherapy is one of the most common treatments for cancer; however, it is associated with several side effects, including oral mucositis. Oral mucositis is a debilitating condition characterized by erythema, edema, and ulceration of the oral mucosa, which can significantly reduce patients’ quality of life. Oral hygiene is considered an important preventive measure to reduce its severity. Objective: To determine the relationship between oral hygiene compliance and the severity of oral mucositis in cancer patients undergoing chemotherapy. Methods: This study used a correlational design with a cross-sectional approach. A total of 52 cancer patients undergoing chemotherapy were selected using purposive sampling. Data were collected using an oral hygiene compliance questionnaire and the Oral Assessment Guide (OAG), and were analyzed using SPSS software with the Somers’ d test. Results: Most respondents had a moderate level of oral hygiene compliance (65%), and the majority experienced moderate oral mucositis severity (92.3%). Statistical analysis showed no significant relationship between oral hygiene compliance and mucositis severity. Conclusion: There is no significant relationship between oral hygiene compliance and the severity of oral mucositis in cancer patients undergoing chemotherapy. Implication: These findings suggest that clinical factors such as chemotherapy regimen, dosage, and treatment duration may have a more dominant influence on the severity of oral mucositis than behavioral factors like oral hygiene, highlighting the need for comprehensive clinical management strategies.